A microfluidic device for simultaneous detection of enzyme secretion and elongation of a single hypha - Itani, Ayaka; Shida, Yosuke; Ogasawara, Wataru (Frontiers in Microbiology, 2023)
Filamentous fungi grow through elongation of their apical region by exocytosis and secrete enzymes that can be of commercial or industrial importance. Their hyphae exhibit extensive branching, making it difficult to control hyphal growth for observation and analysis. Therefore, although hyphal morphology and productivity are closely related, the relationship between the two has not yet been clarified. Conventional morphology and productivity studies have only compared the results of macro imaging of fungal pellets cultured in bulk with the averaged products in the culture medium. Filamentous fungi are multicellular and their expression differs between different hyphae. To truly understand the relationship between morphology and productivity, it is necessary to compare the morphology and productivity of individual hyphae. To achieve this, we developed a microfluidic system that confines hyphae to individual channels for observation and investigated the relationship between their growth, morphology, and enzyme productivity. Furthermore, using Trichoderma reesei, a potent cellulase-producing fungus, as a model, we developed a cellulase detection assay with 4-MUC substrate to detect hyphal growth and enzyme secretion in a microfluidic device in real time. Using a strain that expresses cellobiohydrolase I (CBH I) fused with AcGFP1, we compared fluorescence from the detection assay with GFP fluorescence intensity, which showed a strong correlation between the two. These results indicate that extracellular enzymes can be easily detected in the microfluidic device in real time because the production of cellulase is synchronized in T. reesei. This microfluidic system enables real-time visualization of the dynamics of hypha and enzymes during carbon source exchange and the quantitative dynamics of gene expression. This technology can be applied to many biosystems from bioenergy production to human health.